Nitrous oxide-antinociception is mediated by opioid receptors and nitric oxide in the periaqueductal gray region of the midbrain - Emmanouil, Dimitris E. (2007)
Previous studies have shown that nitrous oxide (N(2)O)-induced antinociception is sensitive to antagonism by blockade of opioid receptors and also by inhibition of nitric oxide (NO) production. The present study was conducted to determine whether these occur within the same brain site. Mice were stereotaxically implanted with microinjection cannulae in the periaqueductal gray (PAG) area of the midbrain. In saline-pretreated mice, exposure to 70% N(2)O resulted in a concentration-dependent antinociceptive effect in the mouse abdominal constriction test. Pretreatment with an opioid antagonist in the PAG significantly antagonized the antinociceptive effect. Pretreatment with an inhibitor of NO production in the PAG also significantly antagonized the antinociceptive effect. These findings suggest that N(2)O acts in the PAG via an NO-dependent, opioid receptor-mediated mechanism to induce antinociception.